Major and 5S ribosomal sequences are localized in the same chromosomal region in Conger conger (Anguilliformes, Congridae) - SALVADORI, SUSANNA; CANNAS, RITA; FODDIS IE; DEIANA, ANNA MARIA; COLUCCIA, ELISABETTA (2001)
MAJOR AND 5S RIBOSOMAL SEQUENCES ARE LOCALIZED IN THE SAME CHROMOSOMAL REGION IN Conger conger (ANGUILLIFORMES, CONGRIDAE) Salvadori S., Cau A., Coluccia E., Cannas R., Foddis I.E., Deiana A. M., Dipartimento di Biologia Animale ed Ecologia, Università di Cagliari, Viale Poetto, 1 - 09126 Cagliari, Italy. e-mail: salvador@unica.it Eukaryotic organisms have a high number of ribosomal genes, organized in two different gene families: the major family encoding for 28S, 18S and 5.8S rRNA, localized in nucleolar organizer region (NOR), and the minor family encoding for 5S rRNA; they represent important markers in karyological analysis. In this work we studied their localization and reciprocal relationships in the conger eel, Conger conger L. The major family has been studied by silver staining that evidences the active NORs, by CMA3 that points out the CG richness of the region and by FISH that localizes directly 45 rDNA sequences. These techniques allowed to localize the NOR in only one pair, the smallest pair 19, throughout the entire short arm. The 5S rRNA gene family has been localized by FISH on the short arm of the pair 19, where the NOR was localized, completely interspersed throughout the chromosome arm, suggesting a colocalization of the two gene families. In higher eukaryotes, included fishes, the two ribosomal gene families are commonly located in different chromosome pairs; Conger conger is the first Anguilliformes species showing the presence of the two ribosomal gene families in the same chromosomal region. Among fishes the major and the minor ribosomal gene families have been mapped in closely related loci in S. salar (1) and Oncorhynchus mikiss (2). 1) Morán P, Martínez JL, García-Vázquez E, Pendás AM (1996) Sex chromosome linkage of 5S rDNA in rainbow trout (Oncorhynchus mykiss). Cytogenet Cell Genet 75: 145-150. 2) Pendás AM, Morán P, Freije JP, García-Vázquez E (1994) Chromosome mapping and nucleotide sequence of two tandem repeats of Atlantic salmon 5S rDNA.Cytogenet Cell Genet 63: 31-36.